Figurative Plastik in Deutschland nach 1945 : Informationsblätter II. - Wilhelm-Lehmbruck-Museum, Duisburg (Duisburg : Wilhelm-Lehmbruck-Museum, 1985)
Alvermann, Hans Peter ; Bernhard, Franz ; Christian, Abraham, David ; Cimiotti, Emil ; Croissant, Michael ; Fischer, Lothar ; Goebel, Renate ; Heiliger, Bernhard ; Kalinowski, Horst Egon ; Koenig, Fritz ; Lehmann, Kurt ; etc.
boek